2015
DOI: 10.1167/iovs.14-15646
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Expression and Function in the Posterior Retina: A Novel Signaling Pathway

Abstract: Oxytocin and OXTR are present in the posterior retina, and OXT induces an increase in hfRPE [Ca(2+)]i. These results suggest that the OXT-OXTR signaling pathway is active in the retina. We propose that OXT activation of the OXTR occurs in the posterior retina and that this may serve as a paracrine signaling pathway that contributes to communication between the cone photoreceptor and the RPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
3
24
0
1
Order By: Relevance
“…We have shown previously that the OXT-induced increase in hfRPE [Ca 2+ ] i was reduced by 87% in the presence of 500 nM of the OXTR-specific antagonist, L-371,257, providing strong evidence that the OXT-induced increase in hfRPE [Ca 2+ ] i was mediated through the OXTR, even when a supraphysiologic dose (6μM) was used. 10 The other specific OXTR antagonist, OTA, in this paper also significantly (> 85 %) reduced the Ca 2+ response to OXT (10 μM), further supporting the explicit activation of OXTR in the RPE. Based on these finding, we used 10μM OXT to ensure maximal activation of cells during perfusion experiments.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We have shown previously that the OXT-induced increase in hfRPE [Ca 2+ ] i was reduced by 87% in the presence of 500 nM of the OXTR-specific antagonist, L-371,257, providing strong evidence that the OXT-induced increase in hfRPE [Ca 2+ ] i was mediated through the OXTR, even when a supraphysiologic dose (6μM) was used. 10 The other specific OXTR antagonist, OTA, in this paper also significantly (> 85 %) reduced the Ca 2+ response to OXT (10 μM), further supporting the explicit activation of OXTR in the RPE. Based on these finding, we used 10μM OXT to ensure maximal activation of cells during perfusion experiments.…”
Section: Discussionsupporting
confidence: 68%
“…10 In the present study, we show that OXT increases hfRPE [Ca 2+ ] i through a GPCR-mediated mechanism whereby the OXT binding to OXTR causes downstream activation of PLC and PIP 2 hydrolysis. In addition, we have shown that heterologously expressed Kir7.1 channels in HEK-OXTR cells, as well as endogenous mouse RPE cell Kir7.1 channels are subject to OXTR inhibition.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We have previously determined that cultured human fetal RPE cells express Rb+ sensitive Kir7.1 current similar to what we recorded from wild-type and carrier hiPSC-RPE cells. 19 In our hands, heterozygous expression of equal amounts of wild type and non-functional p.Trp53* mutant protein also does not influence cellular physiology outcome. 1 Given these findings, we reasoned that carrier hiPSC-RPE are a suitable control to compare test results of both gene restoration and translational read-through.…”
Section: Discussionmentioning
confidence: 59%